Static muscle strength trained and untrained of female students - Kopanski R.; Kolachkowski Z.; Rynkewich T.; Pryimakov O.O; Kopanski D.; Walchak Z. (Kharkov National Pedagogical University, 2012)
Static muscle strength is one of the defining characteristics of human motor potential. Standard terms and exclude the impact of short-term measurement techniques for motion and strain measurements, hence the widespread use of Mm measurements in the assessment of fitness of both trained and untrained, healthy subjects and patients undergoing a variety of reasons the process of rehabilitation. The paper deals with static muscle strength (dynamometry back of the hand) of female students trained (n = 38) and untrained (n = 213). Examined relationships between individual measurements and body weight in both groups, the degree of asymmetry of the palmar and the differences in the level of power (at the level of the absolute and relative terms) between the groups. Disclosed according to form the basis of their conclusions.